Towards a European Health Data Ecosystem. (9th December 2020) - IACOB, Nadina; SIMONELLI, Felice
Abstract : The digital health ecosystem is rife with opportunities to improve healthcare through data-driven services in the European Union (EU). The value of health data, in the multiple forms in which they come (from health records to lifestyle data collected by smartphones or wearables), can truly emerge when they are allowed to flow in the ecosystem within a governance framework supported by all relevant stakeholders, with trust as the common and clear thread underpinning it. The coronavirus pandemic has provided an additional impetus for change, showing the importance of coordination and adequate communication between Member States and quality data to inform decision-making. Significant challenges remain, however, in order to achieve a fully integrated European digital health ecosystem, including: (1) the potentially diverging rules set by Member States at the national level and the need for an EU framework for the secondary use of health data; (2) the need for transparency and accountability for sustaining a data-sharing framework involving public authorities, research organisations, industry and citizens; and (3) the need for interoperable data and processes. Taking stock of these challenges, this article puts forward policy recommendations to enable the provision of pan-European data-driven healthcare services and to build a transparent and trustworthy framework for citizens.